Domestic Violence in Rural Serbia: Etiological-Phenomenological Approach - Soković, Snežana; Ranđelović, Višnja (NBP. Nauka, bezbednosti, policija, 2024)
The aim of the paper is to point to the characteristics of domestic violence in rural areas of Serbia. Geographic isolation, traditional social patterns and cultural norms that characterize rural households contribute to the creation and maintenance of violent patterns of behavior in rural areas. Despite the legally guaranteed gender equality and protection against domestic violence, women in rural Serbia are recognized as a group particularly exposed to domestic violence due to the predominantly traditional beliefs and patterns of behavior in villages in Serbia. Therefore, the aim of the paper is to point to the etiological-phenomenological dimension of domestic violence in rural areas of Serbia. It is assumed that domestic violence in rural areas of Serbia is characterized by the high dark figures of the crime due to the fact that it is usually kept as a private matter, so it is difficult to see its real prevalence. For this reason, besides pointing to the characteristics of domestic violence in rural areas of Serbia, the aim of the paper is to point to the reasons for not reporting this violence, in order to contribute to the establishment of adequate responses to this type of violence, in accordance with its specificities.